(untitled) (Andamios, Revista de Investigación Social, 2014)
This article discusses the complexities faced social by public policies to give satisfactory answers in the context of societies functionally differentiated. From the approximation of the theory of social systems argues for second order policies that facilitate transformation processes and social actors that works according to their own logic of operation. It illustrates the problems of the first order approximations, command and control, with the Latin American and Chilean experience in particular.